Analytic Ethics Within the Context of the Ideas of Logical Positivism and Postpositivism - Vabalaitė, Rūta Marija (Problemos, 2000)
The article deals with an evolution of analytical ethics. The merits and deficiencies of Moore’s criticism of metaphysical ethics are examined. The beliefs of deontological intuitivists that there are some judgements of duties that are analytically true are investigated. Attention is paid to the Stevenson's recognition that ethical judgements could be partly confirmed and to his analysis of the contextual background of such judgements. The latest analytic ethics analyses partial confirmation of the already accepted judgements. However, the rightness of acceptance of the general principle of conduct remains unfounded. It is asserted that it is possibly to deduce particular imperatives, if one accepts such a principle. The significance of the social context is started to be recognised. Some theories make efforts to deduce the ethical statements from the facts of human nature but such efforts may be questionable. The investigation of merely particular moral judgements became the object of analytic ethics. Such a destiny does not befall analytic ethics solely. Epistemology and analytic aesthetics has abandoned the program of the precise logical science and turned to the examination of the historical (including contemporary) context too.
Keywords: good; duty; confirmation; evaluative; factual